Role of diffusion weighted imaging in assessment of anterior cruciate ligament pathology - Hossam Gamal Sharkas; Mena Elerian Youssef Ekladious; Lobna Abdelmoneim Habib; Hossam Moussa Sakr (Romanian Medical Journal)
Background. The anterior cruciate ligament (ACL) is a structure that is vital to preserving the knee's normal stability. However, because the ACL is the ligament that sustains injuries the most frequently, it is essential to distinguish between complete and incomplete tears in order to treat patients with incomplete tears without surgery. To diagnose cruciate ligament tears, knee joint magnetic resonance imaging (MRI) is frequently used. But sometimes it's difficult because edema may hide the ligament fibers. ADC mapping may be useful to confirm whether or not the ligament is continuous for an appropriate diagnosis of incomplete tears because it has been demonstrated that ligament fibers are better visible on diffusion weighted imaging (DWI) and ADC mapping. Objective. To ascertain how anterior cruciate ligament (ACL) tears are diagnosed and classified as partial or complete using diffusion-weighted (DW) magnetic resonance imaging (MRI) and to compare it with conventional MRI sequences. Results. For partial tears, 10 cases (50%) were identified using arthroscopy/follow-up, while observer 1 identified 12 cases (60%) and observer 2 identified 9 cases (45%) using DWI/ADC. For complete tears, 10 cases (50%) were identified using arthroscopy/follow-up, while observer 1 identified 8 cases (40%) and observer 2 identified 11 cases (55%) using DWI/ADC. Conclusions. DWI and ADC are useful tools for diagnosing tears, particularly complete tears, but that caution should be exercised when using these techniques to diagnose partial tears.